Excess Molar Properties and Viscosities of Glycerol + Water System at 298.15 to 318.15 K - Lan, Dawei; Liu, Lihua; Dong, Lining; Li, Wenbin; Li, Qiang; Yan, Ligang (Asian Journal of Chemistry, 2012)
In this study, the experimental densities for the binary system of glycerol + water at the temperature range from (298.15 to 318.15) K at intervals of 5 K are reported. Densities of pure liquids and their mixtures were determined using a bicapillary pycnometer. The viscosities were determined with an Ubbelohde capillary viscometer. The experimental results are compared with data published in the previous literatures. The density (r) and viscosity (h) values, the excess molar volumes VmE, viscosity deviations (Dh) of the experimental data, which the calculated results are fitted to a Redlich-Kister equation to obtain the coefficients and estimated the standard deviations between the experimental and calculated values. The calculated VmE values for the glycerol + water system were negative cover whole compositions at all temperatures, while, the viscosity deviations (Dh) of the aqueous glycerol solutions were positive over the major composition range.